Optimization of Growth and Production of Two Kale Varieties Through the Addition of Led Light - Asyar, Ahmad Wildan; Budiman, Budiman; Sugeru, Herik; Samudra, Bagas Elang (Jurnal Biologi Tropis, 2025)
The high demand for water spinach demands increased production through more efficient cultivation techniques. One important factor that affects plant growth and production is lighting. This study aims to optimize the growth and production of two varieties of water spinach by adding LED lights with a certain light spectrum and duration. The study used a Nested Complete Randomized Block Design (RBD) consisting of two factors. The first factor is the light spectrum (L) with 3 levels, namely the red light spectrum of the 18/6 photoperiod (L1), the blue light spectrum of the 18/6 photoperiod (L2), and the red-blue light spectrum of the 18/6 photoperiod (L3). The second factor is the variety of water spinach (V) consisting of two levels, namely the curly water spinach variety (V1) and the lacinato water spinach variety (V2). Each treatment was repeated 4 times so that there were 24 experimental units. Data analysis used ANOVA with a 5% confidence level and further testing using the Duncan test. The results showed that the growth and production of the two varieties of water spinach were more optimal with the addition of the red-blue light spectrum.